Water quality assessment for aquacultivation in Quang Ngai city, Quang Ngai province - Nguyen Van Lam; Van Nu Thai Thien; Luong Van Viet; Nguyen Thi Ha; Vu Thi Thu Hoa; Vo Le Huy Dao (Journal of Forestry Science and Technology, 2024)
Aquatic product development and growth are significantly influenced by the water supply used for aquaculture. Evaluating the water quality available for this activity is vital since Quang Ngai city has been a major hub for the growth of aquaculture in Quang Ngai province. Twelve surface water quality parameters were monitored and analyzed at eight sampling points in the river basins of An Nghia and Tinh Khe communes from May to September 2023. The Water Quality Index (WQI) was calculated, and methods including Principal Component Analysis (PCA), calculation of environmental variable weights based on principal components (PC), and Pearson correlation were used to assess the correlation of the investigated factors. In the river basin of An Nghia and Tinh Khe communes, 12 criteria for the assessment of surface water quality were tracked and examined using 8 sampling locations between May and September in 2023. The degree of linkage was assessed using principal component analysis (PCA), weighting environmental factors based on principal components (PC), and Pearson correlation. The water quality index (WQI) was calculated between the factors of the research. The findings show that: (1) The parameters exceeded the permitted limit: DO, Alkalinity, NH4+, TP, Vibrio SPP, Coliform, TOC, and TN. The two metrics with the greatest levels of pollution among them are Vibrio SPP and NH4+. The WQI index ranges from 52-74 and is within the average water quality range (51-75); (2) PCA analysis reveals that only the first two principal components, PC1 and PC2 can account for 74.39% of the variance, with NH4+ (0.089) having the highest weight; (3) NH4+ and Vibrio SPP content have a strong correlation (r = 0.95), indicating that both of these parameters can be used to evaluate water quality in the study area in general.